Secondhand ebook Travels in the new global garage sale. - Minter, Adam (2019)
"Revelatory, terrifying, but, ultimately, hopeful." - Elizabeth Kolbert, Pulitzer Prize-winning author of THE SIXTH EXTINCTION From the author of Junkyard Planet , a journey into the surprising afterlives of our former possessions. Downsizing. Decluttering. Discarding. Sooner or later, all of us are faced with things we no longer need or want. But when we drop our old clothes and other items off at a local donation center, where do they go? Sometimes across the country-or even halfway across the world-to people and places who find value in what we leave behind. In Secondhand , journalist Adam Minter takes us on an unexpected adventure into the often-hidden, multibillion-dollar industry of reuse: thrift stores in the American Southwest to vintage shops in Tokyo, flea markets in Southeast Asia to used-goods enterprises in Ghana, and more. Along the way, Minter meets the fascinating people who handle-and profit from-our rising tide of discarded stuff, and asks a pressing question: In a world that craves shiny and new, is there room for it all? Secondhand offers hopeful answers and hard truths. A history of the stuff we've used and a contemplation of why we keep buying more, it also reveals the marketing practices, design failures, and racial prejudices that push used items into landfills instead of new homes. Secondhand shows us that it doesn't have to be this way, and what really needs to change to build a sustainable future free of excess stuff.